Utilization of Mechanistic Enzymology to Evaluate the Significance of ADP Binding to Human Lon Protease - Fishovitz, Jennifer; Sha, Zhou; Chilakala, Sujatha; Cheng, Iteen; Xu, Yan; Lee, Irene (Frontiers in Molecular Biosciences, 2017)
Lon, also known as Protease La, is one of the simplest ATP-dependent proteases. It is a homooligomeric enzyme comprised of an ATPase domain and a proteolytic domain in each enzyme subunit. Despite sharing about 40% sequence identity, human and Escherichia coli Lon proteases utilize a highly conserved ATPase domain found in the AAA+ family to catalyze ATP hydrolysis, which is needed to activate protein degradation. In this study, we utilized mechanistic enzymology techniques to show that despite comparable kcat and Km parameters found in the ATPase activity, human and E. coli Lon exhibit significantly different susceptibility to ADP inhibition. Due to the low affinity of human Lon for ADP, the conformational changes in human Lon generated from the ATPase cycle are also different. The relatively low affinity of human Lon for ADP cannot be accounted for by reversibility in ATP hydrolysis, as a positional isotope exchange experiment demonstrated both E. coli Lon and human Lon catalyzed ATP hydrolysis irreversibly. A limited tryptic digestion study however indicated that human and E. coli Lon bind to ADP differently. Taken together, the findings reported in this research article suggest that human Lon is not regulated by a substrate-promoted ADP/ATP exchange mechanism as found in the bacterial enzyme homolog. The drastic difference in structural changes associated with ADP interaction with the two protease homologs offer potential for selective inhibitor design and development through targeting the ATPase sites. In addition to revealing unique mechanistic differences that distinguish human versus bacterial Lon, this article underscores the benefit of mechanistic enzymology in deciphering the physiological mechanism of action of Lon proteases and perhaps other closely related ATP-dependent proteases in the future.